The expression of cytochrome P4502J2 gene and 14, 15 epoxyeicosatrienoic acid level influence the amount of insulin secreted from human mesenchymal stem cell-derived insulin-producing cells - Eldeen, L.A.T. (2021)
The differentiated insulin-producing cells express high levels of pancreatic duodenal homeobox-1 and insulin gene mRNA. It secretes increasing amounts of C-peptide in response to increasing glucose concentrations than undifferentiated cells. The differentiated insulin-producing cells were found to express reduced amounts of cytochrome P450 2J2 gene mRNA and significant low level of 14, 15 epoxyeicosatrienoic acid than the undifferentiated cells. A strong positive correlation between 14, 15 epoxyeicosatrienoic concentrations and C-peptide released from the differentiated insulin-producing cells was noticed.